Áp lực lo lắng trong học tập ngoại ngữ từ góc nhìn tâm lí học tích cực: Tiếp cận định tính qua khung tường thuật - Lê, Công Tuấn; Trịnh, Quốc Lập (Tạp chí Giáo dục, 2025)
Anxiety in foreign language learning is a distinct emotional phenomenon that significantly affects both the learning process and outcomes. Although many studies have explored this topic using various methods and theoretical frameworks, the perspective of positive psychology has received limited attention. This study aims to analyze the characteristics of anxiety among Vietnamese university students through the lens of positive psychology, focusing on reducing negative emotions while promoting positive ones. Data were collected from 11 students who are not majoring in English, with detailed accounts illustrating their psychological transformation during the learning process. The results indicated that learners can leverage personal strengths and supportive socio-cultural factors to overcome anxiety, thereby fostering a more positive and less stressful learning experience. This study enhances our understanding of anxiety in foreign language learning and offers valuable pedagogical implications for teaching and supporting learners.